Genome-Wide Identification and Expression Analysis of Metal Tolerance Protein Gene Family in Medicago truncatula Under a Broad Range of Heavy Metal Stress - El-Sappah, Ahmed H.; Elbaiomy, Rania G.; Elrys, Ahmed S.; Wang, Yu; Zhu, Yumin; Huang, Qiulan; Yan, Kuan; Xianming, Zhao; Abbas, Manzar; El-Tarabily, Khaled A.; Li, Jia (Frontiers in Genetics, 2021)
Metal tolerance proteins (MTP) encompass plant membrane divalent cation transporters to specifically participate in heavy metal stress resistance and mineral acquisition. However, the molecular behaviors and biological functions of this family in Medicago truncatula are scarcely known. A total of 12 potential MTP candidate genes in M. truncatula genome were successfully identified and analyzed for a phylogenetic relationship, chromosomal distributions, gene structures, docking analysis, gene ontology, and previous gene expression. MtMTPs were further classified into three major cation diffusion facilitator (CDFs) groups: Mn-CDFs, Zn-CDFs, and Fe/Zn-CDFs. The structural analysis of MtMTPs displayed high gene similarity within the same group where all of them have cation_efflux domain or ZT_dimer. Cis-acting element analysis suggested that various abiotic stresses and phytohormones could induce the most MtMTP gene transcripts. Among all MTPs, PF16916 is the specific domain, whereas GLY, ILE, LEU, MET, ALA, SER, THR, VAL, ASN, and PHE amino acids were predicted to be the binding residues in the ligand-binding site of all these proteins. RNA-seq and gene ontology analysis revealed the significant role of MTP genes in the growth and development of M. truncatula. MtMTP genes displayed differential responses in plant leaves, stems, and roots under five divalent heavy metals (Cd2+, Co2+, Mn2+, Zn2+,and Fe2+). Ten, seven, and nine MtMTPs responded to at least one metal ion treatment in the leaves, stems, and roots, respectively. Additionally, MtMTP1.1, MtMTP1.2, and MtMTP4 exhibited the highest expression responses in most heavy metal treatments. Our results presented a standpoint on the evolution of MTPs in M. truncatula. Overall, our study provides a novel insight into the evolution of the MTP gene family in M. truncatula and paves the way for additional functional characterization of this gene family.